Краткий обзор некоторых родоплеменных групп тувинцев по данным междисциплинарных исследований : SUMMARY OF SOME FAMILY BREEDING GROUPS OF TUVANS UNDER DATA OF INTERDISCIPLINARY RESEARCHES - Дамба Лариса Доржуевна; Айыжы Елена Валерьевна; Монгуш Борис Борбак-Оолович; Короткова Надежда Александровна; Чернышенко Дмитрий Николаевич; Утриван Петров Сергей Александрович; Олькова Марина Викторовна; Пылев Владимир Юрьевич; Доржу Чодураа Михайловна; Балановская Елена Владимировна; Балановский Олег Павлович (Вестник Тувинского государственного университета. Естественные и сельскохозяйственные науки, 2019)
Комплексное изучение родоплеменных групп является одной из важных проблем в реконструкции этногенеза тувинцев в целом. В данной статье представлен краткий обзор родоплеменных групп тувинцев донгак, иргит, кужугет, соян, тулуш, чооду с привлечением этнографических и генетических данных. По данным полиморфизма Y-хромосомы в генофондах данных родов преобладают «северо-евразийские» гаплогруппыN-L666, N-L708, N-F4205 и Q-M242, а «западно-евразийские» гаплогруппы представлены только гаплогруппой R1a-M198(x458) с разными частотами. «Центрально-азиатский» компонент представлен субветвями гаплогруппы C2-M217и присутствует в генофондах всех изученных родов. В этногенезе тувинцев, в частности, родоплеменных групп донгак, иргит, кужугет, соян, тулуш, чооду, приняли участие различные этнические группы – самодийские, кетские, центральноазиатские – что отразилось в генофондах данных родоплеменных групп. Необходимо комплексное популяционно-генетическое с репрезентативными выборками родоплеменных групп и историко-этнографическое исследование всех родоплеменных групп тувинцев и популяций Сибири и Центральной Азии. : A comprehensive study of tribal groups is one of the important problems in the reconstruction of the ethnogenesis of tuvans in general. This article provides a brief overview of the tribal groups of tuvans Dongak, Irgit, Kuguget, Soyan, Tulush, Choodu with the involvement of ethnographic and genetic data. According to the Y chromosome polymorphism, the gene pools of these tribal groups are dominated by the “North Eurasian” haplogroups N-L666, N-L708, N-F4205 and Q-M242, and the “Western Eurasian” haplogroups are represented only by the haplogroup R1a-M198 (x458) with different frequencies. The “Central Asian” component is represented by the sub-branches of the haplogroup C2-M 217 and is present in the gene pools of all the tribal groups studied. In the ethnogenesis of the Tuvans, in particular, the tribal groups Dongak, Irgit, Kuguget, Soyan, Tulush, Chood, various ethnic groups took part Samoyed, Ket, Central Asian which was reflected in the gene pools of these tribal groups. A comprehensive population-genetic analysis with representative samples of tribal groups and a historical-ethnographic study of all tribal groups of Tuvans and populations of Siberia and Central Asia are needed.